Safety of participants of criminal trial and ensuring balance of interests of charge and protection - Epikhin, Alexander Yu. (2018)
Ensuring the safety of participants in criminal proceedings is one of the important guarantees for the achievement of the goal of modern Russian criminal justice: involvement of a guilty person or release of an innocent person from punishment. The achievement of this important result can be based on an assessment of the evidence obtained. The citizens' assistance to establish evidence in the work of law enforcement agencies causes certain contradictions. The interests of the state in combating crime and the legitimate interests of a citizen can be asymmetric. In this regard, the state shall create the necessary and sufficient conditions for motivating such assistance. Otherwise, the citizen is not able to potentially assist in the criminal proceedings, as this constitutes a threat to his/her (close relatives) interests. It is particularly relevant to define the optimal balance of state and personal interests in the criminal proceedings. The citizens can facilitate the investigation only when they feel completely safe. At the same time, not only witnesses and victims (their relatives) shall be provided with the protective measures, but a suspect (accused), who promotes criminal justice, as well. The article presents an analysis of the formation and development of the personal security institution in the Russian criminal process. The articles shows the main problems of balancing the interests of the state in combating crime and ensuring the legitimate personal interests of a citizen.